Exploring the intersection of diversity and gaming a case study on Neon, the Filipino character in Valorant - Labor, Johanne Benedict C.; Carreon, Shane L. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
This study analyzes Riot Games' Valorant, a popular first-person shooter known for its diverse roster of characters. Focusing on Neon, a character representing Filipino culture, the research examines player perspectives on character portrayal and inclusivity through content analysis of videos from January 2022 to 2023. By prioritizing cultural references, the study demonstrates how video games can reflect diverse experiences, challenge stereotypes, and promote cross-cultural understanding. This study aims to contribute insights that can foster inclusivity in both gaming and society.
Thesis (Bachelor of Arts in Communication)--UP Cebu, 31 May 2024.
Includes bibliographical references and appendices.